GENDER AND VARIATIVE REPRESENTATION OF REFLECTIONS ON LOVE BY ZINAIDA GIPPIUS - Elena V. Pedchenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article is devoted to the study of the gender problems of the life and work of Zinaida Gippius as the realization of the idea of a human actor and the embodiment of the game elements of the era, which continues and expands the already existing discourse in literary studies. The gender-variable representation of the philosophy of love is considered in the author’s fiction and documentary prose. The psychological and creative motivations of gender searches Gippius, the desire to destroy gender stereotypes and create a new concept of love are determined. The study of the Contes d’amour diary (1893-1904) testifies to a deep introspection, a creative perception of life and a rich inner world of the writer’s experiences, which she hid in a carnival image. The main leitmotif of the diary is the search for “wonderful” love, the desire to feel what “is not in the world”. It formulated the main components of her erotic utopia: kiss, amorousness, rejection of physical intimacy. Her desire for gender equality was laid down by her father’s education and realized in a marriage with Dmitry Merezhkovsky. In marital relations, she values mutual understanding and “mutual knowledge” much more than the sensual manifestations that she leaves for “amorousness”. In same-sex love, she also does not accept physical intimacy, but Gippius was interested in her representatives the opportunity to combine male and female, as a “hint of bisexuality”. In his games of bisexuality and experiments with gender roles, Gippius uses masks of a virgin, a fatal woman, a boy or a man, referring to dressing up, a parody and pseudonyms. Appearance, demeanor and extraordinary abilities gave rise to legends and poetic and mystical nicknames “Petersburg Kassandra”, “La Sylphide”, “Green-eyed naiad”, “White Devil”, but most often she was called the “Decadent Madonna”, which corresponded to the position of the mistress of the house-salon new time, the knightly image of Merezhkovsky and her other admirers. In fiction, Gippius transfers Eros from the sphere of the globe to the “mysterious” space through love (“Miss May”, “Apple in Blossom”, “Twilight of the Spirit”, “Damn Doll”). She represents a “new woman” who does not want to take on the responsibilities of a wife, mother, housewife, but does not reject love and does not become a fighter for women’s rights. Gippius calls her “enlightened,” because a new truth has been revealed to her – faith; this woman knows the “secret” of love and directs her to the One whose love is projected onto the feelings of people. Even if the narrator is a boy or a man, falling in amorousness and the behavior of heroes that destroy stereotypes remain the main ones (“Eternal Femininity”). In exile, Gippius formulates a fairly clear idea of love and gender in the articles “On Love” and “The Arithmetic of Love”, which prove that gender identity, atypical for her time, is inspired by the desire for androgyny.